Comprehensive Transcriptome Analysis Reveals the Role of lncRNA in Fatty Acid Metabolism in the Longissimus Thoracis Muscle of Tibetan Sheep at Different Ages - Bao, Gaoliang; Li, Shaobin; Zhao, Fangfang; Wang, Jiqing; Liu, Xiu; Hu, Jiang; Shi, Bingang; Wen, Yuliang; Zhao, Li; Luo, Yuzhu (Frontiers in Nutrition, 2022)
Long non-coding RNA (lncRNA) plays an important regulatory role in mammalian adipogenesis and lipid metabolism. However, their function in LT muscle of fatty acid metabolism of Tibetan sheep remain undefined. In this study, fatty acid and fat content in longissimus thoracis (LT) muscle of Tibetan sheep were determined, and RNA sequencing was performed to reveal the temporal regularity of lncRNA expression and the effect of lncRNA-miRNA-mRNA ceRNA regulatory network on lipid metabolism of LT muscle in Tibetan sheep at four growth stages (4-month-old, 4 m; 1.5-years-old, 1.5 y; 3.5-years-old, 3.5 y; 6-years-old, 6 y). The results indicated that intramuscular fat (IMF) content was highest at 1.5 y. Moreover, the monounsaturated fatty acid (MUFA) content in 1.5 y of Tibetan sheep is significantly higher than those of the other groups (P<0.05), and it was also rich in a variety of polyunsaturated fatty acids (PUFA). A total of 360 differentially expressed lncRNAs (DE lncRNAs) were identified from contiguous period transcriptome comparative groups of 4 m vs 1.5 y, 1.5 y vs 3.5 y, 3.5 y vs 6 y and 4 m vs 6 y, respectively. KEGG enrichment analysis found the target genes in lncRNA trans-mRNA were significantly related to the protein digestion, absorption and fatty acid biosynthesis pathways (P<0.05). Which demonstrated that DE lncRNA trans-regulated the target genes, and further regulated the growth and development of the LT muscle and intramuscular fatty acid metabolism in Tibetan sheep. We further analyzed the role of lncRNA-miRNA-mRNA regulatory network in the lipid metabolism of Tibetan sheep. And GPD2, LIPE, TFDP2, CPT1A, ACACB, ADIPOQ and other mRNA related to fatty acid and lipid metabolism, and the corresponding lncRNA-miRNA regulatory pairs were identified. The enrichment analysis of mRNA in the regulatory network found that AMPK signaling pathway was the most significantly enriched (P=0.0000112361). Comprehensive transcriptome analysis found that the LIPE, ADIPOQ, ACACB and CPT1A were regulated by lncRNA might change the formation of energy metabolism in Tibetan sheep muscle through the AMPK signaling pathway, and oxidized muscle fibers are transformed into glycolytic muscle fibers, reduced IMF content, and the fatty acid profile also changed.